The effect of eye-foot coordination, leg muscle strength and mental skills on the shooting skills of bangka football school athletes (Gladi : Jurnal Ilmu Keolahragaan, 2022)
This study aims to determine the effect of eye-foot coordination, leg muscle strength, and mental skills on the shooting skills of Bangka Football School athletes. The research method used is an associative quantitative approach with non-test techniques, while the analysis technique uses a path analysis approach. This research was conducted at SSB Selindung 89, Bangka, aged 9-12 years, totaling 36 people. To measure shooting skills, use a ball shooting skill test which is placed at a point 8 m in front of the goal/target. Test your eye-foot coordination by kicking the ball against a wall or the Threebox Wall Soccer Test. Test leg muscle strength using a leg dynamometer with three trials. While the mental skills test uses a questionnaire. Conclusions from the results of the study 1) Eye-foot coordination has a direct effect on shooting skills by 34.1%. 2) Leg muscle strength has a direct effect on shooting skills by 45.3%. 3) Mental skills directly affect shooting skills by 35.4%. 4) Eye-foot coordination has a direct effect on mental skills by 23.5%. 5) Leg muscle strength has a direct effect on mental skills by 44.8%. 6) Eye-foot coordination has an indirect effect on shooting skills of athletes through mental skills of 50.7%. 7) Leg muscle strength has an indirect effect on athletes' shooting skills through mental skills of 43.8%. Keywords: Eye-Foot Coordination, Leg Muscles, Mental Skills, Shooting